Cardiac Cell Culture Technologies Microfluidic and On-Chip Systems (Springer International Publishing, 2018)
Microfluidic systems for cardiac cell culture are discussed based on tested cells and the methods of cardiac cell stimulation; The use of stem cell stimulation into cardiac cells in microfluidic systems is discussed in the context of electrical, biochemical, physical, and mechanical stimulations; Provides an overview of the measurements and data that can be extracted from on-chip systems for use in diagnostics, drug discovery and screening, and clinical therapy. This book provides an introduction to the biological background of heart functioning and analyzes the various materials and technologies used for the development of microfluidic systems dedicated to cell culture, with an emphasis on cardiac cells. The authors describe the characterization of microfluidic systems for cardiac cell culture and center their discussion of the use of stem cell stimulation based on four different types: electrical, biochemical, physical, and mechanical. This book is appropriate for researchers focused on on-chip technologies and heart studies, students in bioengineering and microengineering courses, and a variety of professionals, such as biotechnologists, biomedical engineers, and clinicians working in the cardiac diseases field.